ANALYSIS OF THE TERM METAPHOR THROUGH LITERATURE - Barziyev, Oybek Xabibullayevich; Xayitova, Shohsanam Shuhratjon qizi (INTERNATIONAL CONFERENCES, 2022)
As we know, the word is considered the most important tool in literature due to its importance to make the meaning of your work clearer and more impressive. This work is dedicated to using metaphor in one of different genres and finding aim of writers to use in their work. So as to do analysis, “Animal farm” by George Orwell can be a good example as it is about animal at the farm.